Toward a Positive Theory of Information Evaluation. - Schepanski, Albert; Uecker, Wilfred (The Accounting Review, 1983)
Abstract This research tests a normative model of information evaluation as a descriptive representation of information evaluator (IE) behavior in judging the value of alternative information systems. The criterion of predictive ability was the principal basis for performing this test. Several methodological and design features were introduced which permitted a more rigorous test than was possible in previous studies, IEs specified the amount that they would pay for an information system consisting of a single marble drawn from one of two urns containing many black and white marbles. The sample result was provided to a decision maker who decided from which urn the marble was drawn. Five levels of priors, information system accuracy, and three types of decisionmaker models were experimentally manipulated. The results were inconsistent with the predictions of the normative model. Among the alternative representations we tested, IE behavior was best represented by a multiplicative composition of priors, accuracy, and type of decision maker.